2011
DOI: 10.1093/occmed/kqr181
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health of Turkish Aegean small-scale fishermen

Abstract: In Turkey, small-scale fishermen experience a significant number of health problems and have unhealthy lifestyles. Interventions designed to improve working conditions of small-scale fishermen could help to reduce the number of occupational injuries, which in turn may impact positively on their health. Prevention policies to reduce alcohol and tobacco consumption should also be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 6 publications
5
55
0
3
Order By: Relevance
“…Daily alcohol consumption of at least 300 mL or more was declared by 34% of the sample and 19% reported a consumption of 500 mL or even more per day, which is a finding in agreement with the international experience about fishermen's alcohol abuse [17].…”
Section: Discussionsupporting
confidence: 87%
“…Daily alcohol consumption of at least 300 mL or more was declared by 34% of the sample and 19% reported a consumption of 500 mL or even more per day, which is a finding in agreement with the international experience about fishermen's alcohol abuse [17].…”
Section: Discussionsupporting
confidence: 87%
“…17 These possibly explain the gastrointestinal, respiratory and cardiovascular symptoms commonly reported by them. 18 A study conducted with people of various professions in Taiwan in order to identify the health disparity between them showed that there is a prevalence of two to four times more Cardiovascular Disease (CVD) in fishermen compared to other professions such as machine operators, models and sellers. The same study also found that fishermen are often engaged with smoking and alcohol consumption concurrently and that this association increases the risk of liver disease.…”
Section: Discussion Category 1) Drinking: a Risk Factor Associated Wimentioning
confidence: 99%
“…28 Alcohol abuse was identified as the highest risk factor for accidents and fatal injuries to sailors and fishermen, 29 being the possible facilitating factor for falls resulting in fractures of intervertebral discs. 18 As suggested by Jaremin e Kotulak, 18,30 alcohol can contribute to human errors in navigation and is associated with at least ¼ of accidents, further highlighting the importance of prevention policies to reduce alcohol consumption. 18 Fishing communities have a high level of overall alcohol consumption, as identified in the studied texts.…”
Section: Category 2) Alcohol Consumption and Occupational Accidents: mentioning
confidence: 99%
“…Em termos de prevenção secundária, a lavagem imediata dos olhos 16 , a não mobilização do agente perfurante e o encaminhamento imediato para um atendimento emergencial em ambiente hospitalar foram indicados como importantes variáveis para um desfecho mais favorável 31 . Nos níveis da promoção e da gestão em saúde, as medidas educativas sobre modos de vida saudáveis e prevenção de acidentes também foram memoradas, bem como o imperativo para a implementação de políticas de saúde específi-cas e assistência especializada para os trabalhadores da pesca 7,26,28,30 . Seis artigos não citaram qualquer informação sobre fatores de proteção 18,[21][22][23][24]32 .…”
Section: Fatores De Proteçãounclassified
“…A atividade pesqueira é associada a elevadas taxas de morbidade, de letalidade e de graves lesões decorrentes da atividade 7,8 , em grande parte advindas de fatores intervenientes, de ampla heterogeneidade e naturezas, desde o ambiente de trabalho hostil, tempo de confinamento prolongado, desempenho de funções fisicamente estafantes, exposição a longas jornadas de trabalho e climas extremos, até fatores sociais, econômicos e culturais 9 . Não obstante, houve pouco progresso na incorporação desses conhecimentos às práticas governamentais ao redor do mundo; e, seguindo essa tendência mundial, também no Brasil ainda não houve precisa identificação e resolução dos problemas de saúde relativos à atividade pesqueira, bem como na operacionalização dos serviços e pesquisas em saúde nessa área.…”
Section: Introductionunclassified